2011
DOI: 10.1016/j.tourman.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Employment experiences of Polish migrant workers in the UK hospitality sector

Abstract: The research explores the experiences of Polish migrant workers in the UK hospitality sector. It reports quantitative and qualitative empirical data on the migrants' reasons for entering the hospitality workforce and their subsequent employment experiences. The findings reveal the main motive for entering employment in hospitality is for self development as migrants wish to use and learn foreign languages, gain work experience and receive other benefits that the sector provides.These self development opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 68 publications
(104 reference statements)
1
123
1
1
Order By: Relevance
“…This suggests that majority of the migrants are in low paid employment and to compensate their household expenses, they claim working tax credits. This is consistent with the earlier findings of Janta et al (2011), who found that migrants employed in the hotel industry in the UK are on lower wages. Another interesting observation is that since one third of the migrants meet the prerequisites of claiming working tax credits (i.e., one must be employed or has worked in the UK to make this claim), this suggests that migrants come to the UK for work and not to merely claim social benefits as suggested by the earlier literature (see Boeri, 2010;Drinkwater and Robinson, 2013).…”
Section: Access To the Dolesupporting
confidence: 93%
“…This suggests that majority of the migrants are in low paid employment and to compensate their household expenses, they claim working tax credits. This is consistent with the earlier findings of Janta et al (2011), who found that migrants employed in the hotel industry in the UK are on lower wages. Another interesting observation is that since one third of the migrants meet the prerequisites of claiming working tax credits (i.e., one must be employed or has worked in the UK to make this claim), this suggests that migrants come to the UK for work and not to merely claim social benefits as suggested by the earlier literature (see Boeri, 2010;Drinkwater and Robinson, 2013).…”
Section: Access To the Dolesupporting
confidence: 93%
“…However, there are distinctive features to the tourism consumption patterns of migrant workers that have important implications for tourism flows and market segmentation. With labour migration increasing (see Janta et al, 2011), trips from the new home back to the birthplace or old home become a common occurrence (Duval, 2003), for not only visiting friends and relatives, but also to access services, such as medical or dental care. Connell (2013) accordingly notes that a large portion of international medical travel is by diasporic populations.…”
Section: Under-researched Segmentsmentioning
confidence: 99%
“…Several studies indicate that the hospitality and tourism industry has historically relied on migrant workers (Christensen-Hughes, 1992;King, 1995;Janta et al, 2011;Baum, 2012). Further, Janta et al (2011) also emphasize that migrant tourism labors make work and a casual lifestyle as a combination by engaging in seasonal employment as well as having entertainment and gain life experiences in tourism.…”
Section: International Migrant Labors In Tourism and Hospitality Indumentioning
confidence: 99%